Flat panel displays : advanced organic materials - Kelly, S. M. (Royal Society of Chemistry, 2000)
Liquid crystals and electroluminescent organic materials have a wide commercial application in flat panel displays, in products such as clocks, navigational aids and laptop computers. Traditionally there has been a divide between the two fields of organic materials research and industrial activity. This book aims to bridge that gap and provide a standard reference work for all those involved. Starting with the first prototype and moving chapter by chapter through developments to the present day, Flat Panel Displays: Advanced Organic Materials describes the display type device specifications and material development. With clear descriptions and diagrams, the reader is presented with the fundamental properties of liquid crystals and electroluminescent organic compounds, along with the mode of operation of the displays using them. Written in a non-mathematical way, this book will be welcomed by chemists, physicists and materials scientists in both industry and research.
Keywords: Liquid crystal displays -- Materials.; Electroluminescent display systems -- Materials.; elektronické knihy; electronic books